SHORT CIRCUIT CURRENT LIMIT CONTROL - Pobihailo, V. A. (Systems and Technologies, 2018)
The scientific and practical relevance of improving the functioning of creditlimit short – circuit (short circuit), formulated the goal and objectives ofresearch. As a solution proposed research and the way to manage complexlimitation of short circuit currents in electricity supply production systems underthe reactor – controlled shunt. The algorithm of the system reactor – controlledshunt. For the first time the schemes cause – effect relationships occurrence ofshort – circuit currents – Figure Ysikavy according to ISO 9004.